Considerations on Initiatives to Promote The Application of Material Flow Cost Accounting: Evidence from India - Husain , Shahid; Abdelraheem , Abubkr Ahmed Elhadi; Imam , Ashraf; Khan , Imran Ahmad (International Journal of Accounting and Economics Studies, 2025)
Material flow cost accounting (MFCA) has attracted attention as a representative method of environmental management accounting. However, there are many cases in India where companies have stopped applying MFCA after its introduction. This study examines the criteria for the successful application of MFCA. It conducts a comparative analysis of Pacelile, a company that has applied MFCA for a long time, and Saersa Corporation, a company that stopped MFCA after applying MFCA for a certain period, focusing on the process after the introduction of MFCA. The case study will focus on the process after the introduction of MFCA and conduct a comparative analysis of the two companies. Through these case studies, we will explore the desired forms of MFCA implementation and the efforts to realize those forms.
Keywords: environment, MFCA, suspension, continuation, resumption, efforts